Advances in Control System Technology for Aerospace Applications - Feron, Eric.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
This book is devoted to Control System Technology applied to aerospace and covers the four disciplines Cognitive Engineering, Computer Science, Operations Research, and Servo-Mechanisms. This edited book follows a workshop held at the Georgia Institute of Technology in June 2012, where the today's most important aerospace challenges, including aerospace autonomy, safety-critical embedded software engineering, and modern air transportation were discussed over the course of two days of intense interactions among leading aerospace engineers and scientists. Its content provide a snapshot of today's aerospace control research and its future, including Autonomy in space applications, Control in space applications, Autonomy in aeronautical applications, Air transportation, and Safety-critical software engineering.
Spacecraft Autonomy Challenges for Next-Generation Space Missions -- New Guidance, Navigation and Control Technologies for Formation Flying Spacecraft and Planetary Landing -- Aircraft Autonomy -- Challenges in Aerospace Decision & Control: Air Transportation Systems -- From Design to Implementation: an Automated, Credible Auto coding Chain for Control Systems.
Keywords: Control engineering; Aerospace engineering; Astronautics; Control and Systems Theory; Aerospace Technology and Astronautics